Spectrum of Haematological malignancies managed at tertiary centre: A one-year retrospective review - Anjan Shrestha (Society of Surgeons of Nepal, 2018)
Introduction: Hematological malignancies are not uncommon and all ages and genders are affected. Hematological malignancies are a group of cancers that arise from a malignant transformation of cells of the bone marrow or lymphatic system. There are several classification systems for Hematological Malignancies. The WHO classification was the first worldwide consensus classification on hematological tumors.